Developing a Superhydrophilic/Underwater Superoleophobic Plasma-Modified PVDF Microfiltration Membrane with Copolymer Hydrogels for Oily Water Separation - Hasan Ali Hayder; Peng Shi; Sama M. Al-Jubouri (Applied Sciences, 2025)
Polymer membranes often face challenges of oil fouling and rapid water flux decline during the separation of oil-in-water emulsions, making them a focal point of ongoing research and development efforts. Coating PVDF membranes with a hydrogel layer equips the developed membranes with robust potential to mitigate oil fouling. However, developing a controllable thickness of a stable hydrogel layer to prevent the blocking of membrane pores remains a critical issue. In this work, atmospheric pressure low-temperature plasma was used to prepare the surface of a PVDF membrane to improve its wettability and adhesion properties for coating with a thin hydrophilic film of an AM-NaA copolymer hydrogel. The AM-NaA/PVDF membrane exhibited superhydrophilic and underwater superoleophobic properties, along with exceptional anti-crude oil-fouling characteristics and a self-cleaning function. The AM-NaA/PVDF membrane achieved high separation efficiency, exceeding 99% for various oil-in-water emulsions, with residual oil content in the permeate of less than 10 mg/L after a single-step separation. Additionally, it showed a high-water flux of 5874 L/m2·h for crude oil-in-water emulsions. The AM-NaA/PVDF membrane showed good stability and easy cleaning by water washing over multiple crude oil-in-water emulsion separation and regeneration cycles. Adding CaCl2 destabilized emulsions by promoting oil droplet coalescence, further boosting flux. This strategy provides a practical pathway for the development of highly reusable and oil-fouling-resistant membranes for the efficient separation of emulsified oily water.